Crosslinking type biodegradable POF heat shrinkage film and preparation method thereof
The cross-linked biodegradable POF heat-shrinkable film, with its three-layer structure and specific material combination, solves the problem of poor tear resistance of conventional films at low temperatures, achieving high toughness and tear resistance in low-temperature environments, thus ensuring the reliability and stability of packaging.
Patent Information
- Application Number
- CN202511912804.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-18
- Publication Date
- 2026-01-16
- Estimated Expiration
- 2045-12-18
AI Technical Summary
Conventional biodegradable POF heat shrink film has poor tear resistance at low temperatures, making it prone to tearing and unable to effectively protect the packaged product, thus reducing the reliability and stability of the packaging.
A three-layer cross-linked biodegradable POF heat-shrinkable film enhances the film's toughness and tear resistance through the synergistic effect of LLDPE with different melt indices and toughening agents. Specific measures include using PP as the main raw material, a combination of LLDPE-A, LLDPE-B, and metallocene LLDPE, a combination of POE and EVA as toughening agents, and appropriate irradiation cross-linking doses for the surface and intermediate layers to form a stable network structure.
It significantly improves the tear resistance of heat shrink film under low temperature conditions, ensuring that it is not easily torn in low temperature environments, thereby enhancing the reliability and stability of packaging.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of heat shrinkable film, in particular to a cross-linked biodegradable POF heat shrinkable film and a preparation method thereof. BACKGROUND
[0002] POF heat shrinkable film occupies an important position in the packaging field due to its many advantages such as non-toxic and environmentally friendly, high transparency, high shrinkage rate, good heat sealing performance, high gloss, toughness, tear resistance, uniform heat shrinkage, and suitability for full-automatic high-speed packaging. It is mainly used for packaging regular and irregular shaped products, and is widely used in the packaging of many products such as automotive products, plastic products, stationery, books, electronics, circuit boards, earphones, handicrafts, photo frames, wooden products, toys, pesticides, daily necessities, food, cosmetics, canned beverages, dairy products, medicine, video tapes, etc. With the continuous development of various industries, the demand for POF heat shrinkable film is also increasing, and its market prospect is very broad.
[0003] In the past, when preparing POF heat shrinkable film, linear low-density polyethylene was usually used as the middle layer, and copolymerized polypropylene was used as the inner and outer layers, which were then prepared through extrusion, stretching, cooling and other processes. This preparation method is a relatively common and traditional means in the industry. By controlling the materials and process parameters of different layers, POF heat shrinkable film with certain performance can be obtained, which meets the packaging needs of some products. In the long-term production practice, this method has been continuously optimized and improved, and has become a relatively mature technical means.
[0004] However, the conventional biodegradable POF heat shrinkable film has obvious defects. When the film shrinks and is under low temperature conditions, its tear resistance is poor. This leads to the fact that when used in some low temperature environments, the heat shrinkable film is prone to tearing, which cannot well protect the packaged products and reduces the reliability and stability of the packaging. SUMMARY
[0005] In order to solve the above technical problems, the present application provides a cross-linked biodegradable POF heat shrinkable film and a preparation method thereof, which effectively improves the low-temperature tear resistance of the heat shrinkable film through the synergistic effect between LLDPE with different melt indexes and toughening agents.
[0006] The first aspect of the present application is to provide a preparation method of a cross-linked biodegradable POF heat shrinkable film, which adopts the following technical scheme: A preparation method of a cross-linked biodegradable POF heat shrinkable film, the heat shrinkable film comprises three layers of films that are sequentially attached, the first layer of film and the third layer of film each contain the following raw materials in percentage by weight: PP 89.5-94%, degradation master batch 2-6%, opening agent 0.5-3%, slip agent 1-4%; The second layer film comprises the following raw materials by weight percentage: LLDPE-A 30-35%, toughening agent 9-14.5%, degradation master batch 0.5-1%, LLDPE-B 40-45%, metallocene LLDPE 10-15%, the toughening agent is composed of POE and EVA with a weight ratio of 1: (0.5-1); The melt index of the LLDPE-A is 2.5 g / 10 min, the melt index of the LLDPE-B is 2.1 g / 10 min, and the melt index of the metallocene LLDPE is 1.0 g / 10 min; The preparation thereof comprises the following preparation steps: S1, according to the formula amount, the raw materials are weighed and mixed uniformly, then added into three film layer extruders, plasticized, and then extruded into a co-extrusion die to obtain a first film bubble, and after traction and water cooling, a first film body is obtained; S2, after traction and preheating, the first film body is blown, then sequentially air-cooled, tractioned, and irradiation crosslinked to obtain a POF heat-shrinkable film; the irradiation crosslinking comprises surface layer irradiation and intermediate layer irradiation, the surface layer irradiation electron beam energy is 80 kev, and the irradiation dose is 25-30 kGy, the intermediate layer irradiation electron beam energy is 300 kev, and the irradiation dose is 80-100 kGy.
[0007] By adopting the above technical scheme, PP is selected as the main raw material in the first layer film and the third layer film, which has good rigidity and toughness itself, and provides a certain basic strength for the heat-shrinkable film; the degradation master batch can make the heat-shrinkable film have biodegradable performance; the opening agent can prevent the adhesion between the film layers and ensure the normal use of the film; the slip agent can improve the surface slipperiness of the film, facilitating processing and use.
[0008] In the second layer film, LLDPE-A, LLDPE-B and metallocene LLDPE have different melt indexes, the melt index of LLDPE-A is 2.5 g / 10 min, the flowability is relatively good, and it can be better mixed with other raw materials during processing; the melt index of LLDPE-B is 2.1 g / 10 min, which has good toughness while ensuring a certain flowability; the melt index of metallocene LLDPE is 1.0 g / 10 min, its molecular chain structure is regular, the crystallinity is high, and it can improve the strength and toughness of the heat shrinkable film. The toughening agent is matched with LLDPE and metallocene LLDPE, the toughening agent is dispersed in the LLDPE and metallocene LLDPE matrix, when the heat shrinkable film is impacted by external force, the toughening agent can absorb and disperse energy, and prevent crack propagation. At the same time, the LLDPE and metallocene LLDPE with different melt indexes make the entanglement and interaction between molecular chains more complex, forming a more stable network structure, further enhancing the toughness and tear resistance of the heat shrinkable film. The selection and ratio of raw materials of each layer film are combined, so that the crack resistance of the cross-linked biodegradable POF heat shrinkable film under low temperature conditions is significantly improved.
[0009] When the toughening agent is selected as the combination of the above POE and the above EVA, the toughness of the heat shrinkable film can be effectively improved, thereby improving the low-temperature crack resistance of the heat shrinkable film, and the reason may be that the long-chain entanglement density of the POE with low melt index is high, and an energy dissipation zone is formed at low temperature through the high entanglement network, and more physical crosslinking points need to be broken through when the crack propagates. However, when the melt index of POE is too low, the high molecular weight of POE will lead to uneven dispersion in the LLDPE matrix, and instead form stress concentration points, thereby reducing the low-temperature crack resistance of the heat shrinkable film; when the melt index of POE is too high, POE is mainly in the form of short chains, and the molecular weight distribution is narrow, and the low-temperature crack resistance is poor.
[0010] When the VA content in EVA is 18wt%, it has good compatibility with the LLDPE matrix, and it is in a rubbery state at low temperature; when the VA content is greater than 20%, the acetic acid group is easy to migrate to the surface of the film, resulting in poor slip performance; when EVA is combined with POE, the two can produce a synergistic effect at low temperature, POE provides a crosslinking network skeleton, and EVA fills the network gap, so the impact strength is effectively improved compared with a single toughening agent.
[0011] In addition, the surface layer is irradiated by an electron beam with an energy of 80 keV and a dose of 25-30 kGy, and the middle layer is irradiated by an electron beam with an energy of 300 keV and a dose of 80-100 kGy, so that the cross-linked biodegradable POF heat-shrinkable film can achieve good cross-linking effect. The appropriate dose of the surface layer can make the surface of the film have appropriate hardness and wear resistance, so as to ensure that the surface of the film is not easily damaged during use. The appropriate dose of the middle layer can enhance the internal structure stability and toughness of the film, improve the tear resistance of the film, especially improve the tear resistance of the film after shrinkage at low temperature, so as to ensure that the film is not easily torn during use at low temperature, and improve the reliability and stability of the package. The inventor has found through experiments that if the dose of the surface layer is less than 25 kGy, the surface of the film is not cross-linked enough, the hardness and wear resistance are poor, and scratches are prone to occur; if the dose is more than 30 kGy, the surface of the film may be over-cross-linked and become brittle and hard, which affects the flexibility of the film. If the dose of the middle layer is less than 80 kGy, the internal cross-linking of the film is not enough, and the improvement of the tear resistance is not obvious; if the dose is more than 100 kGy, the internal structure of the film may be over-damaged, which leads to the decline of the overall performance of the film.
[0012] Preferably, the EVA contains 18% of vinyl acetate and has a melt index of 2.5 g / 10 min.
[0013] Preferably, the POE has a melt index of 1.0 g / 10 min.
[0014] Preferably, the slip agent is maleic anhydride grafted polyethylene wax.
[0015] By using the above technical solution, maleic anhydride grafted polyethylene wax is used as a slip agent. Compared with oleic acid amide, maleic anhydride grafted polyethylene wax has better stability and can better maintain the performance during the processing of the POF heat-shrinkable film and is not prone to decomposition or volatilization due to high temperature; it has better compatibility with the raw materials of the film layer and can be more uniformly dispersed in the film layer, thereby more effectively reducing the friction coefficient of the surface of the film layer, making the heat-shrinkable film easier to slide and operate during packaging, reducing the adhesion phenomenon, improving the packaging efficiency and quality, and also improving the antistatic performance of the film layer, further improving the comprehensive performance of the heat-shrinkable film.
[0016] Preferably, the degradation master batch contains Ethylene Polyer 70-79% and Metal Salts 21-30% by weight.
[0017] The second aspect of the present application provides a POF heat-shrinkable film obtained by the preparation method of the cross-linked biodegradable POF heat-shrinkable film.
[0018] In conclusion, the present application has the following advantages: by adding toughening agent and metallocene LLDPE to the LLDPE matrix, and further limiting the melt index of LLDPE, the entanglement and interaction between the molecular chains of the matrix after crosslinking are more complex, a stable network structure can be formed, thereby enhancing the toughness and low-temperature tear resistance of the heat shrinkable film. DETAILED DESCRIPTION
[0019] The application will be further described in detail below in combination with examples. All reagents not specified by the manufacturer are conventional reagent products that can be obtained commercially.
[0020] Example 1 A preparation method of a crosslinked biodegradable POF heat shrinkable film, the heat shrinkable film comprising the following raw materials: The POF heat shrinkable film comprises three layers of films that are sequentially attached, the first layer of film and the third layer of film each comprising the following raw materials in percentage by weight: PP 94%, degradation master batch 2%, opening agent 3%, slip agent 1%; The second layer of film comprises the following raw materials in percentage by weight: LLDPE-A 30%, toughening agent 10%, degradation master batch 1%, LLDPE-B 45%, metallocene LLDPE 14%; The melt index of LLDPE-A is 2.5 g / 10 min, the melt index of LLDPE-B is 2.1 g / 10 min, and the melt index of metallocene LLDPE is 1.0 g / 10 min; The degradation master batch in each film layer comprises Ethylene Polyer 70wt%, Metal Salts 30wt%, the CAS number of Ethylene Polyer is 9002-88-4, and the CAS number of Metal Salts is 3353-05-7; The slip agent is maleic anhydride grafted polyethylene wax; The opening agent is silicon dioxide with a particle size of 3-5 μm; The toughening agent is composed of POE and EVA at a weight ratio of 1:0.5, the content of vinyl acetate in EVA is 18%, the melt index is 2.5 g / 10 min, and the melt index of POE is 1.0 g / 10 min; During preparation, the addition amount of each layer of raw materials is controlled according to the total thickness of the heat shrinkable film being 20 μm and the thickness of the middle layer being 12 μm, and the specific steps include the following steps: S1, according to the above formula, the raw materials of each film layer are weighed and mixed uniformly, then added into three film layer extruders, plasticized, and then extruded into a co-extrusion die to obtain a first film bubble, and then a first film body is obtained after traction and water cooling; S2, after traction and preheating of the first film body, inflation is performed with an inflation ratio of 5.5, and then the POF heat shrinkable film is obtained through air cooling, traction, and irradiation crosslinking in sequence; The irradiation crosslinking includes surface layer irradiation and middle layer irradiation, the surface layer irradiation and the middle layer irradiation are performed simultaneously, the surface layer irradiation is performed at an electron beam energy of 80 kev and an irradiation dose of 25 kGy, and the middle layer irradiation is performed at an electron beam energy of 300 kev and an irradiation dose of 80 kGy.
[0021] Example 2 A preparation method of a crosslinked biodegradable POF heat shrinkable film, the heat shrinkable film comprising the following raw materials: The POF heat shrinkable film comprises three layers of films that are sequentially attached, the first layer of film and the third layer of film each comprise the following raw materials in percentage by weight: PP 92%, degradation master batch 4%, opening agent 1%, and slip agent 3%; The second layer of film comprises the following raw materials in percentage by weight: LLDPE-A 35%, toughening agent 14.5%, degradation master batch 0.5%, LLDPE-B 40%, and metallocene LLDPE 10%; The melt index of LLDPE-A is 2.5 g / 10 min, the melt index of LLDPE-B is 2.1 g / 10 min, and the melt index of metallocene LLDPE is 1.0 g / 10 min; The degradation master batch in each layer of film comprises Ethylene Polyer 79 wt% and Metal Salts 21 wt%, the CAS registration number of Ethylene Polyer is 9002-88-4, and the CAS registration number of Metal Salts is 3353-05-7; The slip agent is maleic anhydride grafted polyethylene wax; The opening agent is silicon dioxide with a particle size of 3-5 μm; The toughening agent is composed of POE and EVA at a weight ratio of 1:0.5, the content of vinyl acetate in EVA is 18%, the melt index of EVA is 2.5 g / 10 min, and the melt index of POE is 1.0 g / 10 min; During preparation, the addition amount of each layer of raw material is controlled according to the total thickness of the heat shrinkable film being 20 μm and the thickness of the middle layer being 12 μm, and the specific steps include the following steps: S1, the raw materials of each layer of film are weighed according to the above formula and mixed uniformly, then added into three film layer extruders, plasticized, and then extruded through a co-extrusion die to obtain a first film bubble, and then a first film body is obtained after traction and water cooling; S2, after traction and preheating of the first film body, inflation is performed with an inflation ratio of 5.5, and then the POF heat shrinkable film is obtained through air cooling, traction, and irradiation crosslinking in sequence; The irradiation crosslinking includes surface layer irradiation and middle layer irradiation, the surface layer irradiation and the middle layer irradiation are performed simultaneously, the surface layer irradiation electron beam energy is 80 kev, and the irradiation dose is 30 kGy; the middle layer irradiation electron beam energy is 300 kev, and the irradiation dose is 90 kGy.
[0022] Embodiment 3 A preparation method of a crosslinked biodegradable POF heat shrinkable film, the heat shrinkable film comprises the following raw materials: The POF heat shrinkable film comprises three layers of films that are sequentially attached, the first layer of film and the third layer of film each comprise the following raw materials in percentage by weight: PP 89.5%, degradation master batch 6%, opening agent 0.5%, and slip agent 4%; The second layer of film comprises the following raw materials in percentage by weight: LLDPE-A 30%, toughening agent 9%, degradation master batch 1%, LLDPE-B 45%, and metallocene LLDPE 15%; The melt index of LLDPE-A is 2.5 g / 10 min, the melt index of LLDPE-B is 2.1 g / 10 min, and the melt index of metallocene LLDPE is 1.0 g / 10 min; The degradation master batch in each layer of film comprises Ethylene Polyer 75 wt% and Metal Salts 25 wt%, the CAS registration number of Ethylene Polyer is 9002-88-4, and the CAS registration number of Metal Salts is 3353-05-7; The slip agent is maleic anhydride grafted polyethylene wax; The opening agent is silicon dioxide, and the particle size is 3-5 μm; The toughening agent is composed of POE and EVA in a weight ratio of 1:0.5, the content of vinyl acetate in EVA is 18%, the melt index is 2.5 g / 10 min, and the melt index of POE is 1.0 g / 10 min; During preparation, the addition amount of each layer of raw material is controlled according to the total thickness of the heat shrinkable film being 20 μm and the thickness of the middle layer being 12 μm, and the specific steps include the following steps: S1, the raw materials of each layer of film are weighed according to the above formula amount, mixed uniformly, and then added into three film layer extruders, plasticized, and then extruded into a co-extrusion die to obtain a first film bubble, and then the first film body is obtained after traction and water cooling; S2, the first film body is tractioned and preheated, and then blown up with a blowing ratio of 5.5, and then sequentially air-cooled, tractioned, and irradiation crosslinked to obtain the POF heat shrinkable film; The irradiation crosslinking includes surface layer irradiation and middle layer irradiation, the surface layer irradiation and the middle layer irradiation are performed simultaneously, the surface layer irradiation electron beam energy is 80 kev, and the irradiation dose is 30 kGy; the middle layer irradiation electron beam energy is 300 kev, and the irradiation dose is 90 kGy.
[0023] Example 4 A preparation method of a crosslinked biodegradable POF heat-shrinkable film, which is different from example 1 in that the weight ratio of POE and EVA in the toughening agent is 1:1, and the others are the same as example 1.
[0024] Example 5 A preparation method of a crosslinked biodegradable POF heat-shrinkable film, which is different from example 1 in that only POE is used in the toughening agent, and the others are the same as example 1.
[0025] Example 6 A preparation method of a crosslinked biodegradable POF heat-shrinkable film, which is different from example 1 in that only EVA is used in the toughening agent, and the others are the same as example 1.
[0026] Example 7 A preparation method of a crosslinked biodegradable POF heat-shrinkable film, which is different from example 1 in that the surface layer irradiation dose is 20 KGy, the middle layer irradiation dose is 70 KGy, and the others are the same as example 1.
[0027] Example 8
[0028] A preparation method of a crosslinked biodegradable POF heat-shrinkable film, which is different from example 1 in that the surface layer irradiation dose is 35 KGy, the middle layer irradiation dose is 105 KGy, and the others are the same as example 1.
[0029] Comparative Example 1 A preparation method of a crosslinked biodegradable POF heat-shrinkable film, which is different from example 1 in that an equal amount of LLDPE-B is used instead of metallocene LLDPE, and the others are the same as example 1.
[0030] Performance detection The heat-shrinkable films obtained in the above examples and comparative examples were subjected to shrinkage rate, tensile properties at room temperature, and tear strength at low temperature, and the detection results are shown in Table 1.
[0031] Among them, the shrinkage rate was tested according to the relevant provisions in GB / T 13519-1992 "Polyethylene heat-shrinkable film" at 100℃, and the tensile strength and elongation at break were detected according to the relevant provisions in GB / T13022-1991 "Tensile properties of plastic film"; The tear strength was detected according to ASTM D1922 "Standard test method for tear resistance of plastic films and sheets-pendulum method", the film was frozen at -30±2℃ for 2h, and then the tear performance was detected, and the sample was a rectangular sample with a size of 76mm×63mm.
[0032] Table 1: Performance test results of heat shrinkable film Sample Heat shrinkage (MD / TD) % Tensile strength (MD / TD) MPa Elongation at break (MD / TD) % Tear strength (MD / TD) KN / m Example 1 78 / 80 130 / 135 150 / 155 30 / 32 Example 2 75 / 79 125 / 130 145 / 154 28 / 30 Example 3 76 / 79 126 / 125 144 / 153 29 / 30 Example 4 75 / 80 126 / 128 143 / 154 28 / 32 Example 5 70 / 80 100 / 109 121 / 134 16 / 22 Example 6 71 / 75 105 / 114 116 / 127 12 / 19 Example 7 68 / 75 102 / 112 118 / 130 19 / 24 Example 8 69 / 78 95 / 98 106 / 117 10 / 15 Comparative Example 1 40 / 51 94 / 102 665 / 730 18 / 24 As can be seen from Table 1: The heat shrinkage rates of the POF heat shrinkable films obtained in Examples 1-4 are all above 75% in the MD direction and above 75% in the TD direction, indicating that the POF heat shrinkable films obtained in the present application have good heat shrinkage performance.
[0033] The tensile strengths of the heat shrinkable films obtained in Examples 1-4 are all above 120 MPa in the MD and TD directions, and the elongation at break is above 140% in the MD direction and above 150% in the TD direction, indicating that the heat shrinkable films of the present application have good strength and flexibility. As can be seen from the tear strength data, the tear strength of the heat shrinkable films of the present application can still reach 30 KN / m in the MD direction and 32 KN / m in the TD direction after being frozen at -30°C for 2 h, indicating that the POF heat shrinkable films obtained in the present application have excellent low-temperature crack resistance, effectively prolonging their service life at low temperature.
[0034] Compared with Example 1, when only POE or only EVA is used as the toughening agent in the intermediate layer in Examples 5 and 6, the heat shrinkage rates of the heat shrinkable films obtained in Examples 5 and 6 are reduced, and the tensile strength and elongation at break are significantly reduced compared with Example 1, and the tear strength at low temperature is also significantly reduced compared with Example 1. Therefore, when POE and EVA are used together, a synergistic effect is produced. The reason is that the long-chain entanglement density of POE with a low melt index is high, and a high entanglement network is formed at low temperature to form an energy dissipation zone, and more physical crosslinking points need to be broken when the crack propagates. EVA fills the crosslinking network skeleton provided by POE, so that the impact strength of the two is significantly improved compared with single EVA and POE, thereby significantly improving the impact strength.
[0035] Compared with Example 1, when the irradiation crosslinking dose of the surface layer and the irradiation crosslinking dose of the intermediate layer are lower or higher than the irradiation crosslinking dose defined in the present application, the performance of the heat shrinkable films obtained in Examples 7-8 is reduced, and the performance is significantly reduced when the irradiation dose of the surface layer and the intermediate layer is higher than the upper limit of the present application. This further indicates that the irradiation dose of the present application effectively ensures the performance of the heat shrinkable films of the present application.
[0036] Compared with Example 1, the heat shrinkage rate, tensile strength, elongation at break, and tear strength at low temperature of the heat-shrinkable film obtained by Comparative Example 1 are all significantly reduced, because the LLDPE with different melt indexes and the metallocene LLDPE make the entanglement and interaction between molecular chains more complex, and form a more stable network structure, further enhancing the toughness and tear resistance of the heat-shrinkable film.
[0037] The embodiments of the present specific implementation are the preferred embodiments of the present application, and do not limit the protection scope of the present application, so that: any equivalent changes made according to the structure, shape, principle of the present application should be covered within the protection scope of the present application.
Claims
1. A method for producing a crosslinked biodegradable POF heat-shrinkable film, the heat-shrinkable film comprising a first layer film, a second layer film, and a third layer film sequentially attached, characterized by: The first layer film and the third layer film each comprise the following raw materials in weight percentage: PP 89.5-94%, degradation master batch 2-6%, opening agent 0.5-3%, slip agent 1-4%; The second layer film comprises the following raw materials in weight percentage: LLDPE-A 30-35%, toughening agent 9-14.5%, degradation master batch 0.5-1%, LLDPE-B 40-45%, metallocene LLDPE 10-15%, the toughening agent being composed of POE and EVA in a weight ratio of 1: (0.5-1); The LLDPE-A has a melt index of 2.5 g / 10 min, the LLDPE-B has a melt index of 2.1 g / 10 min, and the metallocene LLDPE has a melt index of 1.0 g / 10 min; The preparation thereof comprises the following preparation steps: S1, the raw materials are weighed according to the formula amount, mixed uniformly, and then added into three film layer extruders, plasticized, and then extruded into a co-extrusion die to obtain a first film bubble, and then the first film body is obtained after traction and water cooling; S2, the first film body is tractioned and preheated, then blown, and then sequentially subjected to air cooling, traction, and radiation crosslinking to obtain a POF heat-shrinkable film; the radiation crosslinking comprises surface layer radiation and middle layer radiation, the surface layer radiation has an electron beam energy of 80 kev and a radiation dose of 25-30 kGy, and the middle layer radiation has an electron beam energy of 300 kev and a radiation dose of 80-100 kGy.
2. The process for the preparation of a cross-linked biodegradable POF heat shrinkable film as claimed in claim 1, wherein: The EVA has a vinyl acetate content of 18% and a melt index of 2.5 g / 10 min.
3. The process for the preparation of a cross-linked biodegradable POF heat shrinkable film as claimed in claim 1, wherein: The POE has a melt index of 1.0 g / 10 min.
4. The process for the preparation of a cross-linked biodegradable POF heat shrinkable film as claimed in claim 1, wherein: The slip agent is a maleic anhydride grafted polyethylene wax.
5. The process for the preparation of a cross-linked biodegradable POF heat shrinkable film as claimed in claim 1, wherein: The degradation master batch comprises Ethylene Polyer 70-79% and Metal Salts 21-30% in weight percentage.
6. A POF heat-shrinkable film obtained by the preparation method of the crosslinked biodegradable POF heat-shrinkable film according to any one of claims 1-5.
Citation Information
Patent Citations
Heavy-duty thermal shrinkage polyethylene film and preparation method thereof
CN102173160A
Biodegradable POF (polyolefin) heat-shrinkable film and preparation method thereof
CN108727705A
Degradable environment-friendly polyolefin thermal contraction film and preparation method thereof
CN110406223A
Crosslinked polypropylene foam material with good cohesiveness and preparation method thereof
CN115612205A
Recyclable POF heat shrink film and preparation method thereof
CN120534039A
Cited By
Radiation crosslinking biodegradable POF heat shrink film and preparation method thereof
CN122185676A
